Neural basis of multi-sensory communication in primates. Issue 3 (4th May 2022) - Sliwa, Julia; Mallet, Marion; Christiaens, Maëlle; Takahashi, Daniel Y.
Abstract : Primates present a rich range of communication strategies in different modalities that evolved as signaling, perceiving and signaling back behaviors. This diversity benefits from specialized dedicated neural pathways for signaling and for perceiving communication signals. The brain areas for perceiving and producing communicative signals can be described separately, but form integrated neural loops, which coordinate perception and action in the signaler and receiver. Moreover, the different sensory modalities are initially processed separately by the brain but eventually share neural pathways for communication: a redundancy that might ensure proper signal transfer. Only a few primate species have been studied so far, including rhesus, long-tailed macaques, squirrel monkeys, marmosets, and humans. Yet, the evidence suggests that all primates possess specialized neural pathways coordinating a diverse range of communication systems for organizing their complex kin and friendship bonds.